Illuminating the impact of CD38-induced adenosine formation in B-cell lymphoma - Shams ElDoha Galal ElDin Zaiema; Heba Mohamed Saber Hafez; Diaa El-Din Moussa Sherif Abou El-Ela; Rawda Ahmed Alaaeldin Ahmed Mohamed Saad (Scientific Reports)
Abstract The expression of CD38 by cancer cells may mediate an immune-suppressive effect by producing Extracellular Adenosine (ADO) acting through G-protein-coupled cell surface receptors on cellular components and tumor cells. This can increase PD-1 expression and interaction with PD-L1, suppressing CD8 + cytotoxic T cells. This study examines the impact of heightened CD38 expression and extracellular ADO on various hematological and clinical parameters in patients with mature B-cell lymphoma, alongside their correlation with the soluble counterparts of the PD-1/PD-L1 axis. Our study was conducted on 90 patients, CD38-positive and CD38-negative (measured by flow cytometry), with mature B-cell lymphoma divided into CLL and B-NHL subtypes. Their serum ADO, soluble PD-1, and PD-L1 levels were measured using a sandwich ELISA. Our study revealed a positive correlation between CD38 expression, sADO, sPD-1, and sPD-L1 in mature B-cell lymphoma patients. CD38-positive patients had higher sADO, sPD-1, and sPD-L1 levels. Higher CD38 expression and extracellular ADO negatively affected HB level and PLT count and positively correlated with the higher risk stratification in mature B-cell lymphoma patients. This study explored the potential impact of CD38 expression and elevated extracellular ADO on B-cell lymphoma alongside their link with the PD-1/PD-L1 axis. Our findings underscore the influence of extracellular ADO on the neoplastic process of mature B-cell lymphoma. We also propose targeting the CD38-induced-ADO formation pathway, which could serve as a promising therapeutic immune target with multifaceted effects within mature B-cell neoplasms.